RESULTS OF STUDYING THE INFLUENCE OF BIO-FERTILIZER “YER MALHAMI” ON THE QUALITY OF WATER BODIES - Guzal F. Sherkuzieva; Feruza I. Salomova; Firuza U. Yuldasheva (Central Asian Journal of Medicine, 2023)
The biofertilizer is intended for pre-sowing treatment of seeds and seedlings of vegetables, industrial crops, potatoes, roots of young seedlings of fruit trees, forest crops in order to accelerate plant growth, increase yield, improve its quality, and suppress phytopathogenic microflora. The "Yer malkhami" has been shown to be effective in agricultural trials, which requires the development of maximum permissible concentrations.